Detecting subtle yet fast skeletal muscle contractions with ultrasoft and durable graphene-based cellular materials. Issue 4 (5th October 2021) - He, Zijun; Qi, Zheng; Liu, Huichao; Wang, Kangyan; Roberts, Leslie; Liu, Jefferson Z; Liu, Yilun; Wang, Stephen J; Cook, Mark J; Simon, George P; Qiu, Ling; Li, Dan
Abstract: Human bodily movements are primarily controlled by the contractions of skeletal muscles. Unlike joint or skeletal movements that are generally performed in the large displacement range, the contractions of the skeletal muscles that underpin these movements are subtle in intensity yet high in frequency. This subtlety of movement makes it a formidable challenge to develop wearable and durable soft materials to electrically monitor such motions with high fidelity for the purpose of, for example, muscle/neuromuscular disease diagnosis. Here we report that an intrinsically fragile ultralow-density graphene-based cellular monolith sandwiched between silicone rubbers can exhibit a highly effective stress and strain transfer mechanism at its interface with the rubber, with a remarkable improvement in stretchability (>100%). In particular, this hybrid also exhibits a highly sensitive, broadband-frequency electrical response (up to 180 Hz) for a wide range of strains. By correlating the mechanical signal of muscle movements obtained from this hybrid material with electromyography, we demonstrate that the strain sensor based on this hybrid material may provide a new, soft and wearable mechanomyography approach for real-time monitoring of complex neuromuscular–skeletal interactions in a broad range of healthcare and human–machine interface applications. This work also provides a new architecture-enabled functional soft material platform for wearable electronics. Abstract : Stretchable graphene foam enables a new wearable mechanomyographic strategy for monitoring subtle yet fast skeletal muscular activities.